PENGARUH CASH HOLDING, FINANCIAL CONSTRAINT, DAN INVESTMENT OPPORTUNITIES TERHADAP AUDIT FEE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2016- 2019) - Ayu Novita Simanullang; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of cash holding on audit fees which is moderated by financial constraints and investment opportunities. This research refers to research conducted by (Mohammadi et al., 2018).Cash holding, financial constraints and investment opportunities have a positive influence on audit costs. This is in accordance with the hypothesis and based on agency theory. This study uses multiple regression analysis, classical assumption test, t test, f test and determinant coefficient test.This study found that cash holding has no relationship with audit fees. The moderating variable for financial constraints has a positive relationship with audit fees, while investment opportunities have a negative relationship with audit fees